Essential invertebrates - Krekelberg, Alyssa (2022)
Examines Earth's invertebrates, highlighting a diverse selection of 22 notable species from around the world. A blend of narrative text, authoritative nonfiction content, fact boxes, and vivid photos bring these amazing invertebrates to life. Features include a glossary, online resources, source notes, and an index.
Includes bibliographical references (pages 106) and index.
Ages 8-13
Keywords: Invertebrates -- Juvenile literature; Invertebrates -- Behavior -- Juvenile literature; Animals -- Identification -- Juvenile literature; Zoology -- Juvenile literature